I never promised you a rose garden - Green, Hannah 1932- (New York : New American Library, 1964)
Chronicles the three-year battle of a mentally ill, but perceptive, teenage girl against a world of her own creation, emphasizing her relationship with the doctor who gave her the ammunition of self-understanding with which to destroy that world of fantasy.
Keywords: Psychotherapist and patient -- Fiction; Teenage girls -- Fiction; Mentally ill -- Fiction; Mental illness -- Fiction; Psychological fiction